Taurine Antioxidant Effect in Decreasing Kidney Damage in Male Mice (Mus Musculus) due to Oxidative Stress Induced by Paraquat - Pratama, Ricki; Hestianah, Eka Pramyrtha; Widiyatno, Thomas Valentinus; Meles, Dewa Ketut; Kurnijasanti, Rochmah (Universitas Airlangga, 2021)
Paraquat toxicity occurs through the high production of reactive oxygen species (ROS) which cause damage due to oxidative stress. Antioxidants can reduce damage through prevention of oxidative stress. Taurine has shown the ability to act as an antioxidant. The aim of this research is to find a effect of antioxidant taurine to decrease kidney damage caused by oxidative stress due to paraquat by looking at the histopathology changes. 25 male adult mices from strain DDY were used and divided into five treatment groups; C(-) (Aquadest IP), C(+) (Paraquat 30mg/kg), P1 (Paraquat 30mg/kg + Taurine 250mg/kg), P2 (Paraquat 30mg/kg + Taurine 500mg/kg) and P3 (Paraquat 30mg/kg + Taurine 1000mg/kg). All groups were given treatment intraperitoneal for twenty one days. The mices were sacrificed where kidney were collected for histopathology preparation. The parameters measured were renal histopathological changes in form of degeneration and necrosis. The results show that taurine administration had an effect on decreased degrees of damage to kidney tubular cells, with a decrease in the mean degree of renal tubular degeneration and necrosis. Degeneration of renal tubular cells in groups (P2) reduced compared to the group (C+) there were significant differences (P <0.05). Necrosis of renal tubular cells in groups (P1, P2) reduced compared to the group (C+) there were significant differences (P <0.05). In conclusion, this research proves that administration of paraquat causes renal histopathological changes which are characterized by degeneration and necrosis. It also proves that taurine dose of 500 mg/kgBB could provided optimal effect.